What is ‘Theory’ in Grounded Theory? - Kara L. Vander Linden (Grounded Theory Review: An International Journal, 2022)
Theory is often discussed in relation to research. However, despite its frequent reference, there is a lack of consensus on what theory is. This article briefly discusses some views of theory within sociology and the lack of consensus over what constitutes theory. This lack of consensus makes it important that grounded theorists not only explain what is meant by a theory being grounded in data but also what is meant by theory in grounded theory.